La municipalisation de la gestion urbaine par la concertation. Le cas du Comité de Concertation de Tabriquet à Salé (Maroc) - Coline Mias (L’Année du Maghreb)
The following article examines the municipal management style of the Justice and Development Islamiste Party (PJD) and its reconfiguration in the light of the late institutional and political reforms that fostered local and participative governance in Morocco. Through a local study case, a Concertation Committee located in one of the electoral bastions of the PJD, Tabriquet’s district in the city of Salé, we intend to analyse the politization displays of this participatory arrangement, depicted as favoring technicians and urban policy experts over local elected representatives. Thus, we aim at underlying the interactions, but also the tensions existing between those political actors in the territorial production. Despite the complex relationship that prevails between the royal palace and the PJD regarding the legalization of a party with an « Islamic » baseline, the later gave substance to the decentralization measures driven by the Moroccan state for years. In fact, the PJD contributed to promote a participatory style in its urban management, enhancing a local system of actors and thereby managing to create, for its own benefit, autonomous spaces distinct from the traditional decisional channels.